iPETLIN Petlin Database Management System - Abdul Rahman bin Abdullah, Abdul Rahman (Universiti Teknologi PETRONAS, 2012)
iPETLIN- Petlin Database Management System is a project to build a web application to provide a database management system by setting up a standard data model with a standard record keeping procedure. The long time taken to reach the resources, the variety of documents used to store data and data anomalies are the problems which are expected to be reduced and solved once the project is implemented. The scope of study for this project building a web application and database management system in a company, Petlin (Malaysia) Sdn Bhd. Taking Extreme Programming as its guidance to build the web application, this project is expected to finish in a short time. Based on the surveys done, most of the staff agreed that all problems in the company happen many times in their working days.